Strengthening Family Economic Resilience through Greenhouse-Based Horticulture - Suyana, Hilma; Budiman, Andika Nuraga; Yugaswara, Heri (Entrepreneurship and Community Development, 2025)
This community service program aims to strengthen family economic resilience through horticultural development using the greenhouse method in Mandalamekar Village, Bandung. The main problem faced by the community was the destruction of the existing greenhouse following a natural disaster in 2023, which disrupted agricultural production sustainability and affected food security. The program was implemented through persuasive and participatory action approaches involving local farmers, village officials, lecturers, students, and alumni. The implementation stages included training, facilitation, mentoring, and monitoring of the greenhouse construction and horticultural management processes. Evaluation was conducted using pre- and post-test methods to measure improvements in participants’ knowledge and skills. The results show that greenhouse-based horticulture contributes to increasing agricultural productivity, farmers’ income, and household food resilience. In addition, the program supports achieving university performance indicators (IKU 2, 3, and 5), which encourage off-campus learning and collaboration between academia and the community. The program provides significant managerial implications in developing sustainable agricultural innovation, empowering local farmers, and utilizing appropriate technology to support economic recovery and resilience in rural areas. This initiative serves as a model for strengthening rural economies through environmentally adaptive and technology-based agriculture.